2017
DOI: 10.1016/j.meatsci.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ultrasonic technology for continuous monitoring of pork loin and ham dry salting

Abstract: Online ultrasound measurements were taken using pulse-echo mode in loins (Longissimus dorsi) and hams at different salting times (up to 30days). From the time-domain ultrasonic wave, the time of flight (TOF) was computed as well as its variation between two signals (ΔTOF). A progressive decrease in TOF during dry salting was found, which was linked to the salt gain, water loss and the reduction in sample thickness. Predictive models based on the ultrasonic parameters (ΔTOF and initial time of flight, TOF) corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Until now, commented results are obtained using the through-transmission mode, namely a method in which two transducers are connected directly at both sides of the sample (De Prados et al, 2017). That is the reason why it can be very difficult to introduce this mode of application in certain stages of the dry-cured ham process.…”
Section: Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, commented results are obtained using the through-transmission mode, namely a method in which two transducers are connected directly at both sides of the sample (De Prados et al, 2017). That is the reason why it can be very difficult to introduce this mode of application in certain stages of the dry-cured ham process.…”
Section: Ultrasoundmentioning
confidence: 99%
“…However, the pulse-echo mode allows to simplify its implementation in the process, considering that only one transducer is positioned in the sample, working as emitter and transducer at the same time (Awad et al, 2012). Traditionally, this mode has been applied for the detection of defects in metallic materials, although its use for the characterization of components in food has been recently investigated (De Prados et al, 2017). By measuring the Time of Flight variation (ΔTOF) of the pulse-echo mode it is possible to monitor the salting process in hams with a mean thickness of 15.7 cm (De Prados et al, 2017), showing a high ΔTOF reduction at few hours after the beginning of the salting (De Prados et al, 2016).…”
Section: Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…During dry‐curing, salt crystals must first dissolve and be absorbed into the meat matrix to effect water removal. However, various factors, including meat chemical characteristics, fat content, and age, have a remarkable impact on NaCl uptake during dry‐curing, 56 which will invariably affect water expulsion. Thus, to achieve maximum moisture loss, the meat product may have to be cured for an extended period.…”
Section: Resultsmentioning
confidence: 99%
“…Graiver, Pinotti, Califano, and Zaritzky () have also provided mathematical relations governing the uptake of curing salts in pork meat. Factors including meat chemical characteristics, fat content, pH, age, and species among others have been identified to influence NaCl uptake during curing (de Prados, Garcia‐Perez, & Benedito, ; Vestergaard, Andersen, & Adler‐Nissen, ). Another study (Quilaqueo & Aguilera, ) also identified salt morphological characteristics, specifically size and shape as important factors that influence salt crystal dissolution and uptake, and concluded these may be important variables to consider in the drive to achieving sodium reduction while maintaining the overall quality and acceptability of foods.…”
Section: Introductionmentioning
confidence: 99%